PENGARUH JENIS DAN KONSENTRASI PUPUK DAUN TERHADAP PERTUMBUHAN DAN HASIL TANAMAN TERUNG (Solanum melongena L.) VARIETAS MUSTANG F1 - Muhammad Isnaini, Abdul Rahmi, dan Akas Pinaringan Sujalu (Agrifor : Jurnal Ilmu Pertanian dan Kehutanan, 2014)
Objectives of the research were to study the effect of type and concentration  foliar fertilizer, as well as their interaction on the growth and yield of Eggplant; and to find proper type and consentration of foliar fertilizer for better growth and production of Eggplant.  The research was carried out from July to October 2012, since preparation of growing media until crop harvested.  It was held at Experiment at Simpang Pait Village, Long Ikis Subdistrict, Paser District, Provinsi of East Kalimantan.   The research employed Completely Randomised Design (CRD) with factorial 2 x 5 experiment and 4 replications.  The first factor was type of foliar fertilizer (J), that consisted of two levels, namely:  Green Tonik (j1), and Supranik (j2). The second factor was concentration of foliar fertilizer (K), that consisted of five levels, namely: no foliar fertilizer as control (k0); 1,0 ml l-1 water (k1); 2,0 ml l-1 water (k2); 3,0 ml l-1 water (k3), and 4,0 ml l-1 water (k4).  Results of the experiment indicated that : (1) foliar fertilizer types (J) affect very significantly on plant height at 28, 42, and 56 days after planting, but it did not affect significantly on plant height 14 days after planting, blooming time, harvest time, number of fruit, and weight of fruit; (2) concentration of foliar fertilizer (K) affect significantly on plant height at 14, 21, 28 and 42  days after planting, and weight of fruit, but it did not significantly on blooming time, harvest time, and number of fruit.  The highest weight of fruit was attained on the 4,0 ml l-1 water treatment (k4) with 0,58 kg plant-1 while the worst one was on the no foliar fertilizer treatment (k0) with 0,49 kg plant-1; and (3) the interaction between those two factors did not affect significantly on all parameters observed, but it did affect significantly on plant height 24 days after planting.